2006
DOI: 10.1176/ajp.2006.163.8.1355
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Utilization in Jerusalem Under Terrorism

Abstract: Except for the elderly and previously hospitalized persons, Jerusalem residents did not increase their use of psychiatric services but did increase their use of some other health services. These results suggest that this terrorism-affected population did not perceive their mental and social suffering as requiring specialized intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…This may be both due to the fact that our study documented DD on first admission of all hospitalized psychiatric patients and not lifetime rates, and the lower prevalence of an alcohol-related disorder in the general adult population of Israel (about 4%; Neumark et al, 2007). The increase in incidence rates from 2000 to 2003, particularly in the younger age group, may be associated with the intensive terroristic attacks (Al-Aqsa Intifada) that exerted stress-induced effects on terror-affected population (Levav et al, 2006;Schiff et al, 2007). This explanation may be supported by the study of alcohol use in New York after the terrorist attacks (Boscarino et al, 2006), showing that greater exposure to the World Trade Center disaster was associated with greater alcohol consumption during the first two years and with binge drinking at 1 year after this event, as well as with alcohol dependence, assessed as present in either year 1 or year 2.…”
Section: Main Findingsmentioning
confidence: 99%
“…This may be both due to the fact that our study documented DD on first admission of all hospitalized psychiatric patients and not lifetime rates, and the lower prevalence of an alcohol-related disorder in the general adult population of Israel (about 4%; Neumark et al, 2007). The increase in incidence rates from 2000 to 2003, particularly in the younger age group, may be associated with the intensive terroristic attacks (Al-Aqsa Intifada) that exerted stress-induced effects on terror-affected population (Levav et al, 2006;Schiff et al, 2007). This explanation may be supported by the study of alcohol use in New York after the terrorist attacks (Boscarino et al, 2006), showing that greater exposure to the World Trade Center disaster was associated with greater alcohol consumption during the first two years and with binge drinking at 1 year after this event, as well as with alcohol dependence, assessed as present in either year 1 or year 2.…”
Section: Main Findingsmentioning
confidence: 99%
“…Por ejemplo, en Israel tras los ataques con misi-les SCUD durante la guerra del Golfo en 1991 aumentaron las consultas urgentes y disminuyeron las programadas, el número de consultas de medicina general se redujo a la mitad pero el de consultas de salud mental aumentó 24 . De hecho, el estrés producido por los incidentes terroristas hizo que las consultas por problemas médicos triviales disminuyeran mientras que las consultas por problemas psicopatológicos como ansiedad o somatización aumentaron 25,26 . El estudio ya citado de Baca et al realizado en víctimas del terrorismo en España ha encontrado un aumento de la frecuencia de trastornos del ánimo y de trastornos de ansiedad con respecto a la población general, además de un aumento en el abuso de alcohol entre las víctimas directas.…”
Section: Terrorismo Y Servicios Sanitariosunclassified
“…For example, research after major traumatic events present either no significant increment of psychotropic drug use (Druss & Marcus, 2004; Boscarino et al 2005) a minimal increment (McCarter & Goldman, 2002) or even less use compared with a non-exposed control group (Goldberg et al 2013). In addition, a small increase of anxiolytic prescription by non-psychiatrists was observed after 9/11 (Druss & Marcus, 2004), as well as a small increment in visits to primary care physicians (Rosenheck & Fontana, 2003; Levav et al 2006), suggesting that individuals might seek help in non-psychiatric settings. Still, other studies did not show this pattern (Rosenheck & Fontana, 2003; Goldberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The slight increase in treatment seeking after a mass traumatic event observed at times in the general population might be due to specific 'at risk' populations, such as older populations who may have previously been exposed to severe traumas (e.g., the Holocaust (Levav et al 2006)), or individuals with severe mental illness (SMI). Indeed research has robustly shown individuals with severe mental problems to be especially prone to difficulty in managing high or even moderate levels of stress (Lira & Jutta, 2012; Palmier-Claus et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation